Synchronization of ovulation and timed artificial insemination to improve fertility in postpartum dairy cows - Rajeswari T (Department of Animal Reproduction, Gynaecology and Obstetrics, College of Veterinary and Animal Sciences, 2008)
The present research work was undertaken to evaluate different oestrus synchronization protocols and to recommend a better and more consistent timed artificial insemination (TAI) protocol for improving fertility in postpartum dairy cows. The study was performed in 30 crossbred cows at day 40 postpartum belonging to University Livestock Farm, Mannuthy during the period from July 2007 to May 2008. Efficacy of various synchronization protocols for inducing oestrus and ovulation and conception rate in the experimental and control groups were determined.